Potential use of Trichinella spiralis antigen for serodiagnosis of human capillariasis philippinensis by immunoblot analysis - Pewpan M. Intapan (2018)
Intestinal capillariasis is an emerging helminthic zoonosis caused by Capillaria philippinensis and is frequently fatal if not diagnosed correctly. The present study demonstrates cross-reactivity between Trichinella spiralis larval antigens and C. philippinensis-infected human sera by immunoblotting. Sera from 16 proven intestinal capillariasis patients and 16 proven trichinosis patients were tested. The antigenic patterns recognized by intestinal capillariasis sera varied with the molecular masses, ranging from less than 20.1 to more than 94 kDa. The immunoblotting profiles of the trichinosis sera were similar to those of the intestinal capillariasis sera. The antigenic bands with 100% reactivity were located at 36.5, 40.5, and 54 kDa, respectively. Sera from patients with trichuriasis, strongyloidiasis, opisthorchiasis, and healthy controls differed clearly from the previous two and produced very faint patterns of reactivity and attenuated bands. This assay is potentially useful for large-scale screenings of persons at risk for C. philippinensis infection. Parasitological stool examinations of the positive cases are necessary as secondtier laboratory tests for confirming the diagnosis. © Springer-Verlag 2005.